Myelinated fibres in human paravertebral sympathetic chain: white rami communicantes in alcoholic and diabetic patients - Appenzeller, Otto (1974)
White rami communicantes were studied quantitatively in patients with chronic alcoholism or diabetes mellitus. The fascicular area of interganglionic segments of the paravertebral sympathetic chain showed less variation than that previously reported for controls. Fibre densities were higher in the patients than in controls of similar age and the percentage of small fibres in alcoholics and diabetics is larger than in controls. Only 17% of fibres were larger than 5 μm in diameter in the patients, whereas, in controls, 33% of fibres were larger than 5 μm in diameter. No correlation between internodal lengths and fibre diameter was found in the patients who showed uniformly short internodes averaging only about half of internodal distances found in control subjects. The uniformly short internodes are attributed to complete degeneration followed by partial regeneration and are compatible with either Wallerian degeneration or a `dying back' phenomenon. The short internodal lengths should be reflected in slowed conduction velocities in white rami communicantes and could account for abnormalities in baroreflex activity, sweating, and in visceral dysfunction commonly seen in patients with chronic alcoholism or diabetes.